Na1.5Rb0.5PO3F·H2O: synthesis, properties, and stepwise reconstruction of the hydrogen bond network. Issue 20 (8th September 2021) - Yang, Xin-Rui; Liu, Xin; Wang, Zujian; Deng, Xue-Bin; Lu, He-Jie; Li, Yu-Jia; Long, Xifa; Chen, Ling; Wu, Li-Ming
Abstract : The precise substitution of NH4 + with Na + /Rb + cations in NPF·H2 O leads to a stepwise reconstruction of the hydrogen bond networks from NPF·H2 O, NNPF·H2 O to NRPF·H2 O, giving rise to the symmetry and optical property tunings. Abstract : We report a new DUV transparent (<200 nm) noncentrosymmetric Na1.5 Rb0.5 PO3 F·H2 O compound crystallizing in the Pmn 21 space group. This compound exhibits the second largest birefringence in the monofluorophosphate family, Δ n obv. = 0.04 at 546 nm, which is attributed to the nearly uniform alignment of the P–F bonds. The SHG response is observed to be 0.55 × KDP at 1064 nm. More interestingly, the precise substitution of NH4 + with Na + /Rb + cations in the well-known structure (NH4 )2 PO3 F·H2 O leads to a stepwise reconstruction of the hydrogen bond networks, which eventually alters the crystal symmetry and the optical properties.